2022
DOI: 10.3390/ijms23042319
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Affects Fatty Acids Profiling and Key Synthesis Genes Expression Patterns in Zanthoxylum bungeanum Maxim

Abstract: Zanthoxylum bungeanum is one of the most important medicinal and edible homologous plants because of its potential health benefits and unique flavors. The chemical components in compositions and contents vary with plant genotype variations and various environmental stress conditions. Fatty acids participate in various important metabolic pathways in organisms to resist biotic and abiotic stresses. To determine the variations in metabolic profiling and genotypes, the fatty acid profiling and key differential ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Overall, we observed that lipids accumulated in higher quantities in XY15 as compared to GX74 except 10-hydroxydecanoic acid, docosanoic acid (behenic acid), and arachidic acid ( Table S2 ). These observations generally support earlier reports that increasing the contents of lipids/fatty acids in the membrane lipids can enhance cold resistance in low-temperature environments [ 23 , 24 ]. Similar to the lipids, the amino acids and their derivatives’ contents increased in rapeseed siliques after cold-stress treatment, indicating that cold induces their biosynthesis.…”
Section: Resultssupporting
confidence: 91%
“…Overall, we observed that lipids accumulated in higher quantities in XY15 as compared to GX74 except 10-hydroxydecanoic acid, docosanoic acid (behenic acid), and arachidic acid ( Table S2 ). These observations generally support earlier reports that increasing the contents of lipids/fatty acids in the membrane lipids can enhance cold resistance in low-temperature environments [ 23 , 24 ]. Similar to the lipids, the amino acids and their derivatives’ contents increased in rapeseed siliques after cold-stress treatment, indicating that cold induces their biosynthesis.…”
Section: Resultssupporting
confidence: 91%
“…Under low-temperature stress, unsaturated fatty acids in plants are beneficial to maintain the stability of cell membranes [ 15 , 34 ]. In this study, the content of free fatty acid in seedlings propagated from 5-year-old P. orientalis donors was higher than that from 2000- and 3000-year-old ones, and the content was highest in cutting seedlings and least in sown seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 13 ]. With an increase in donor age, the production of flavonoid compounds in the phenylpropanoid biosynthesis pathway might be adversely affected in Ginkgo biloba L. [ 14 , 15 ]. The activities of various key enzymes of the phenylpropanoid biosynthetic pathway, such as Phenylalanine ammonialyase (PAL) and Chalcone synthase (CHS), were variably regulated under abiotic stresses [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…USFAs can increase the fluidity of the membrane, which is very important for activating the enzymes on the membrane. In plants, the higher USFA contents in membrane lipids can result in the temperature of transition of membrane lipids, which increases plant resistance to cold stress [ 12 ]. Therefore, the degree of USFAs in plant cell membrane directly determines the fluidity of the membrane and affects the resistance of plants to abiotic and biotic stresses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%